The Influence of Customer Experience, Customer Relationship, and Payment Terms on Purchase Intention: Pengaruh Pengalaman Pelanggan, Hubungan dengan Pelanggan, dan Persyaratan Pembayaran terhadap Niat Pembelian - Rumefi, Ufi (Indonesian Journal of Law and Economics Review, 2023)
This study investigates the impact of Customer Experience, Customer Relationship, and Term of Payment on Purchase Intention within the context of a specific customer base. Employing a quantitative approach with a descriptive correlational design, the research encompasses 41 participants. Data was gathered through a Likert Scale questionnaire and analyzed using multiple linear regression in SPSS V16.0. The findings reveal that Customer Experience, Customer Relationship, and Term of Payment collectively contribute to 79.5% of the variance in Purchase Intention, with the remaining 20.5% attributed to unexamined factors. Notably, Customer Relationship emerges as the most influential factor, while Term of Payment exhibits no significant effect on Purchase Intention. This study advances our understanding of the nuanced interplay between customer-centric factors and purchase decisions, offering implications for enhancing customer engagement strategies. Highlights: Quantifying Impact: Investigating the influence of Customer Experience, Customer Relationship, and Term of Payment on Purchase Intention in a specific customer context. Customer Relationship Primacy: Highlighting the paramount significance of Customer Relationship as the key driver of Purchase Intention among consumers. Payment Terms and Influence: Demonstrating that Term of Payment does not significantly impact Purchase Intention, providing valuable insights for marketing strategies and consumer behavior. Keywords: Customer Experience, Customer Relationship, Term of Payment, Purchase Intention, Consumer Decision